Metaphors and Social Identity Formation in Paul's Letters to the Corinthians - Lim, Kar Yong. (Eugene : Wipf and Stock Publishers, 2017)
Why did Paul frequently employ a diverse range of metaphors in his letters to the Corinthians? Was the choice of these metaphors a random act or a carefully crafted rhetorical strategy? Did the use of metaphors shape the worldview and behavior of the Christ-followers? In this innovative work, Kar Yong Lim draws upon Conceptual Metaphor Theory and Social Identity Theory to answer these questions. Lim illustrates that Paul employs a cluster of metaphors--namely, sibling, familial, temple, and body metaphors--as cognitive tools that are central to how humans process information, construct reality.
Description based upon print version of record.
Added to collection customer.56279.3 - Master record variable field(s) change: 072, 082, 630, 650
Keywords: Bible. -- Criticism, interpretation, etc; Bible. -- Criticism, interpretation, etc; Metaphor in the Bible; Group identity -- Biblical teaching; Identification (Religion) -- Biblical teaching; RELIGION / Biblical Studies / New Testament; RELIGION / Biblical Studies / Paul's Letters; Electronic books